Boosting impact and innovation in higher education - Rynehart, Ross (Emerald Publishing Limited, 2018)
This book provides a practical guide to mastering The Knowledge Entrepreneur Toolkit and to establishing High Diversity Groups in universities. Both are key to universities boosting their capacity for innovation and their impact both internally and on major world issues. This is not a traditional academic book. Rather, it represents a practical and pragmatic guide for academics, professional staff and university leaders to develop the skills and cultures needed to work intelligently and creatively with high levels of diversity. High levels of diversity, intentionally assembled, is the key to high performing leadership groups and research groups within universities. The author challenges academics and professionals within universities to pay as much attention to the development of their inter-personal skills and knowledge as they do to academic and professional skills and knowledge. He suggests that development of these skills has often been neglected, resulting in the inability of universities to realise the full potential of diversity and to create new knowledge and innovations that add value. Long standing university cultures and practices are challenged by this book. Yet universities are being required to adapt rapidly to technological and social changes as well as societal expectations. The Knowledge Entrepreneur and High Diversity Groups are two very timely frameworks to enable universities in meeting these challenges.